Self-regulated learning predicts skill group differences in developing athletes - Bartulovic, D.; Young, B. W.; Baker, J. (Psychology of Sport and Exercise, 2017)
Objectives: Self-regulated learning (SRL) likely plays a crucial role in expert development by helping individuals optimize their practice (Zimmerman, 2006). However, limited sport studies have examined expert/novice differences in SRL, and almost none have used a self-report SRL measure. Therefore, the purpose of this study was to examine SRL differences in three progressively skilled athletic groups: recreationally competitive, less-elite, elite. Design: A cross sectional study using a self-report survey. Method: We vetted the Self-Regulation of Learning-Self-Report Scale (SRL-SRS; Toering et al., 2012) survey for face validity with an expert panel. Subsequently, 272 participants (200m, 72 f; ages 18-35) completed a sport-training version of the SRL-SRS, which included modified items according to panel recommendations and refinements for factorial validity. Participants also completed survey measures for weekly practice and performance level. Logistic regression analyses served to determine: a) how composite (overall) SRL processes, and b) how six constituent SRL processes, explained performance level. Results: Greater overall engagement in composite SRL was associated with being in the elite group compared to less-elite and recreationally competitive groups. Of the constituent SRL processes, only self-monitoring predicted membership in the elite and less-elite group compared to the recreationally competitive. Additional analyses revealed planning, self-monitoring, effort and self-efficacy separately predicted membership in the elite group, relative to the less-elite group, and recreationally competitive group. Conclusions: Elite athletes self-monitor more frequently and may integrate other constituent processes better within a SRL cycle.